Constitutional-Legal and Administrative-Legal Aspects of Statutory Regulation and Maintenance of Public Security in the Russian Federation by the State and Private Actors - YASTREBOVA, Anna I.; STAKHOV, Alexander I.; MERKULOV, Pavel A.; SUCHKOVA, Tatyana Y.; FILONOV, Vladimir I.; MATVEEVA, Evgeniia S. (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
The topicality of the researched problem is caused by the need for the rule-making and law-enforcement activity of the Russian Federation and its constituent entities in the development of scientifically proven, clear and consistently understandable mechanism of public security regulation as well as the arrangement in Russia of an efficient system of state and private actors maintaining the public security, participation of civil institutions in the public security and order maintenance. The article objective is to develop the doctrinal key positions describing the specific features of constitutional-legal and administrative-legal framework of statutory regulation and public security maintenance in the Russian Federation. The dialectic interconnection between the constitutional-legal and administrative-legal means of public security regulation in the Russian Federation is the leading approach to this problem researching. The comparative-legal method, which allows researching the federal legislation and the legislation of constituent entities of the Russian Federation as well as the foreign experience in the researched sphere, is another method. The article contains the analysis of the provisions of the Constitution of the RF and the Federal Law Concerning Security, the determination of scientifically substantiated limits, structure and content of public security as an object of administrative and legal regulation, taking which into account the specific features of activity of the President of the RF, the Security Council as well as the legislative, executive and judicial authorities as the subjects of public security maintenance are described; the substantiation of specific features of activity of private actors maintaining the public security; the analysis of experience of activity of civil institutions participating in the public security maintenance in the foreign countries, including in the USA and Great Britain. The article materials can be used in the domestic and foreign theory of constitutional and administrative law, in the rule-making activity of the Russian Federation and its constituent entities, in the practical activity of executive authorities, citizens and non-governmental organizations, which participate in the implementation of the state policy for the public security maintenance.